2016
DOI: 10.1039/c6ob00401f
|View full text |Cite
|
Sign up to set email alerts
|

Non-redox metal ion promoted oxidative coupling of indoles with olefins by the palladium(ii) acetate catalyst through dioxygen activation: experimental results with DFT calculations

Abstract: Developing new catalytic technologies through C-H bond activation to synthesize versatile pharmaceuticals has attracted much attention in recent decades. This work introduces a new strategy in catalyst design for Pd(ii)-catalyzed C-H bond activation in which non-redox metal ions serving as Lewis acids play significant roles. In the oxidative coupling of indoles with olefins using dioxygen, it was found that Pd(OAc)2 alone as the catalyst is very sluggish at ambient temperature which provided a low yield of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 128 publications
9
40
0
Order By: Relevance
“…However, when the ratio continuously increased from 1 to 2, the efficiency improvement is relatively minor. This phenomenon is similar to those in allylbenzene isomerization, but distinctly different from that in Wacker-type oxidations catalyzed by Pd(OAc) 2 /Lewis acid [33][34][35]. In Wacker-type oxidation, the Sc(III)/Pd(II) ratio of 4 is much more efficient than the ratio of 1.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…However, when the ratio continuously increased from 1 to 2, the efficiency improvement is relatively minor. This phenomenon is similar to those in allylbenzene isomerization, but distinctly different from that in Wacker-type oxidations catalyzed by Pd(OAc) 2 /Lewis acid [33][34][35]. In Wacker-type oxidation, the Sc(III)/Pd(II) ratio of 4 is much more efficient than the ratio of 1.…”
Section: Resultssupporting
confidence: 50%
“…Inspired by these findings, we explored non-redox metal ions as Lewis acid-promoted olefin isomerization and its oxidative coupling with indoles by a Pd(OAc) 2 catalyst. In those reactions, the role of Lewis acid is assigned to improve the C-H bond activation ability of the Pd(II) cation through the formation of heterometallic Pd(II)/Lewis acid (LA) species, and related DFT calculations have supported this assignment [34,35]. Here, we report an example of such a simple Pd(OAc) 2 /LA system in biomass utilization, that is, catalyzing isomerization of methyl linoleate to its corresponding conjugated derivatives, whereas Pd(OAc) 2 alone is inactive.…”
Section: Abstract Biomass Transformation · Methyl Linoleate Isomerizamentioning
confidence: 97%
“…Formation of these bisindoles can be practically suppressed adding AcOH to the reactionmixture. [29] As previously stated, 3-alkenylindoles can be used as dienes in Diels-Alder reactions and this methodc an be exploited for the regioselective synthesis of 1,3-symmetrical carbazoles starting from indoles and a,b-unsaturated carbonyl derivatives (Scheme 7). [30] The alkenylations tep has been demonstrated to be catalyzed by Pd and Cu salts and requiresalarge excess of alkenes for an efficient reaction.…”
Section: C-3 Alkenylationsmentioning
confidence: 99%
“…In this reaction a variable amount of bisindolyl derivatives arising from a Friedel–Crafts reaction of the target 3‐indolyl acrylates with the indole substrates are often observed. Formation of these bisindoles can be practically suppressed adding AcOH to the reaction mixture …”
Section: Transition Metal C−h Activation Of Indoles and Alkenesmentioning
confidence: 99%
“…Evidenced by mechanism studies, the presence of non‐redox metal ions can change the coordination structure of reactive species substantially, which regulates their catalytic activities . The presence of non‐redox metals may also alter the reaction pathway and control the yield distribution of different oxidative products . Particularly in the case of Ru catalysts, we found that the addition of non‐redox metal ions as Lewis acids can accelerate the catalytic epoxidation of olefins and saturated C−C bond dehydrogenation .…”
Section: Introductionmentioning
confidence: 97%